Yen Bloc or Yuan Bloc : An Analysis of Currency Arrangements in East Asia - Shirono, Kazuko (IMF Working Papers; Working Paper ;, 2009)
This paper examines the role of Japan against that of China in the exchange rate regime in East Asia in light of growing interest in forming a currency union in the region. The analysis suggests that currency unions with China tend to generate higher average welfare gains for East Asian countries than currency unions with Japan or the United States. Overall, Japan does not appear to be a dominant player in forming a currency union in East Asia, and this trend is likely to continue if China's relative presence continues to rise in the regional trade.